Biofertilizer Impacts on Soybean [Glycine max (L.)] Cultivation, Humid Tropics | Biological Nitrogen Fixation, Yield, Soil Health and Smart Agriculture Framework. Issue 1 (2022) - Otaiku, Ayodele A.; Soretire, Soretire; A.A, A.A; Mmom, Mmom; C, P.
No abstract available